Auxin Physiology of the Tomato Mutant diageotropica - Daniel, Steven G. (1989)
The tomato (Lycopersicon esculentum, Mill.) mutant diageotropica (dgt) exhibits biochemical, physiological, and morphological abnormalities that suggest the mutation may have affected a primary site of auxin perception or action. We have compared two aspects of the auxin physiology of dgt and wild-type (VFN8) seedlings: auxin transport and cellular growth parameters. The rates of basipetal indole-3-acetic acid (IAA) polar transport are identical in hypocotyl sections of the two genotypes, but dgt sections have a slightly greater capacity for IAA transport. 2,3,5-Triiodobenzoic acid and ethylene reduce transport in both mutant and wild-type sections. The kinetics of auxin uptake into VFN8 and dgt sections are nearly identical. These results make it unlikely that an altered IAA efflux carrier or IAA uptake symport are responsible for the pleiotropic effects resulting from the dgt mutation. The lack of auxin-induced cell elongation in dgt plants is not due to insufficient turgor, as the osmotic potential of dgt cell sap is less (more negative) than that of VFN8. An auxin-induced increase in wall extensibility, as measured by the Instron technique, only occurs in the VFN8 plants. These data suggest dgt hypocotyls suffer a defect in the sequence of events culminating in auxin-induced cell wall loosening.